Intelligibility of English Vocabulary for Young Learners in EFL Context: Digital Book Vs Printed Book on Listening and Pronunciation Skills - Suhartawan Budianto; Nur Sayidah; Sucipto; Nurul Qomariah; Anjangsari Khaida Asaro; Wahyu Fajar Setiawan (JTP - Jurnal Teknologi Pendidikan, 2024)
This study explores young learners’ intelligibility of English vocabulary for young learners in the EFL (English as a Foreign Language) context using Digital Books vs Printed Books which focus on listening and pronunciation skills. The intelligibility was measured from listening tests.  The research is an experimental study with a pretest–posttest control group design. Sixty-one out of 156 elementary level from grade 4th were taken randomly thirty students belonged to the control group while another thirty belonged to the experimental group. This study applied the Mann-Whitney Test. The result showed that young learners with digital books outperformed listening and pronunciation for young learners in the EFL context. In short, digital books with listening and pronunciation are very beneficial for young learners in acquiring EFL vocabulary.